2012
DOI: 10.1016/j.bbrc.2011.12.144
|View full text |Cite
|
Sign up to set email alerts
|

ErbB4 localization to cardiac myocyte nuclei, and its role in myocyte DNA damage response

Abstract: The intracellular domain of ErbB4 receptor tyrosine kinase is known to translocate to the nucleus of cells where it can regulate p53 transcriptional activity. The purpose of this study was to examine whether ErbB4 can localize to the nucleus of adult rat ventricular myocytes (ARVM), and regulate p53 in these cells. We demonstrate that ErbB4 does locate to the nucleus of cardiac myocytes as a full-length protein, although nuclear location occurs as a full-length protein that does not require Protein Kinase C or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
0
17
1
1
Order By: Relevance
“…Moreover, ErbB4 may play a role in DOX-induced myocardial DNA damage [45]. Our results showing that DOX causes a greater increase in ErbB4 than AN-152 may explain the lack of cardiotoxicity so far seen in preclinical and clinical studies with AEZS-108 [24, 25, 27].…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, ErbB4 may play a role in DOX-induced myocardial DNA damage [45]. Our results showing that DOX causes a greater increase in ErbB4 than AN-152 may explain the lack of cardiotoxicity so far seen in preclinical and clinical studies with AEZS-108 [24, 25, 27].…”
Section: Discussionmentioning
confidence: 82%
“…Our results demonstrate that ErbB2 localizes to the peri-nuclear area and ErbB4 localizes to the nucleus in cardiac myocytes of failing type 1 diabetic post-MI hearts, thereby confirming our Western blot analysis. Previous studies have demonstrated that the increased localization of ErbB4 to the nucleus in adult rat ventricular myocytes may be an indicator of cell stress response [23], a finding that has also been observed in other receptor tyrosine kinases [24]. Whether nuclear localization of ErbB receptors affects their availability and/or ability to bind NRG-1 ligands and thereby contribute to the obliteration of compensatory NRG-1/ErbB signaling in the diabetic heart after MI is equally important from a therapeutic standpoint and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other ERBB family members, ERBB4 has been identified in the nucleus of normal and cancer cells (147–149). Most notably, the intracellular domain (ICD) generated by γ-secretase-mediated cleavage of ERBB4, can translocate to the nucleus (150).…”
Section: 2 Her/erbb Familymentioning
confidence: 98%